Broadband synchronization of ultrafast pulse generation with double-walled carbon nanotubes - Zheng Jiancheng; Li Diao; Liu Peng; Cui Xiaoqi; Zhang Bin; Geng Wei; Zhang Qiang; Xu Zhenyu; Kauppinen Esko I.; Sun Zhipei (Nanophotonics)
Double-walled carbon nanotubes have shown competitive properties in broadband optical pulse generation owning to the intrinsic electronic properties. Synchronization of ultrafast optical pulses in multiple wavelengths is a key technique for numerous applications, such as nonlinear frequency conversion, ultrafast pump-probe, coherent Raman scattering spectroscopy, coherent optical synthesis, etc. In this work, we demonstrate the mode-locking and synchronization of 1.55 µm pulses with 1 µm and 1.9 µm pulses via a single saturable absorber based on double-walled carbon nanotubes. The large optical nonlinearity and broadband optical absorption in the double-walled carbon nanotubes enable independent and synchronized mode-locking in >900 nm bandwidth. In addition, we present a creative concept to realize multi-wavelength synchronization from a single laser system. Our results demonstrate a straightforward and feasible approach towards pulse synchronization over ultra-broad bandwidth with flexible wavelength selection in the near-infrared region.